Development of styrene butadiene rubber-butadiene rubber with a hyperelastic model for vehicle tire design - Rachmat, Angki Apriliandi; Ramadhan, Muhammad Hisyam; Mardiyati, Yati; Suweca, I Wayan; Dirgantara, Tatacipta (National Research and Innovation Agency, 2025)
This paper proposes a mathematical correlation between styrene butadiene rubber (SBR)-butadiene rubber (BR) composition and hyperelastic model parameters for numerical studies in vehicle tire design. Experimental, numerical, and curve-fitting methods were employed in this research. Experimental tests were conducted using tensile tests for SBR-BR. The numerical study of the SBR-BR tensile test was carried out using several classic hyperelastic models. The best hyperelastic model was selected based on the smallest deviation between numerical and experimental results. Curve-fitting was done between the best hyperelastic model parameters and the compound to obtain a new correlation, and it was validated. This research shows that the neo-Hookean model with 6 % deviation is the most suitable for the SBR-BR, and the mathematical correlation for SBR-BR composition and C10 is linearly correlated. SBR60 %-BR40 % shows the optimum composition for non-pneumatic tires with the characteristic of maximum tensile strength 16.71 MPa, elongation 251 %, and 200 % modulus 13.04 MPa.